1998
DOI: 10.1046/j.1365-2133.1998.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxydeoxyguanosine in urine as an index of oxidative damage to DNA in the evaluation of atopic dermatitis

Abstract: 8-hydroxydeoxyguanosine (8-OHdG) is one of the products which are excreted in urine as a result of oxidative damage to DNA. We investigated the feasibility of using 8-OHdG in urine as an index for oxidative damage to DNA in atopic dermatitis (AD). Seventeen patients with long-standing AD and 17 healthy volunteers were enrolled in this study. The severity of AD was evaluated by SCORAD index. Eosinophils, total IgE and lactate dehydrogenase-5 in peripheral blood were measured as clinical parameters for AD. A new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 11 publications
(11 reference statements)
0
60
1
1
Order By: Relevance
“…ā€¢ OH generates various products from the DNA bases which mainly include C-8 hydroxylation of guanine to form 8-oxo-7,8 dehydro-2 -deoxyguanosine, hydroxymethyl urea, urea, thymine glycol, thymine and adenine ring-opened, and saturated products [106]. 8-Hydroxyguanine is the most commonly observed product.…”
Section: Dnamentioning
confidence: 99%
“…ā€¢ OH generates various products from the DNA bases which mainly include C-8 hydroxylation of guanine to form 8-oxo-7,8 dehydro-2 -deoxyguanosine, hydroxymethyl urea, urea, thymine glycol, thymine and adenine ring-opened, and saturated products [106]. 8-Hydroxyguanine is the most commonly observed product.…”
Section: Dnamentioning
confidence: 99%
“…32 A commercial ELISA kit is now available (Oxis Research, Portland, OR), and we used this kit to estimate urinary 8-OHdG in Sprague-Dawley rats in a recent study. 33 The technique and procedural details are simple, and the assay is reliable and reproducible.…”
Section: Assay For Urinary and Renal 8-ohdgmentioning
confidence: 99%
“…In animal and clinical studies, the calorie restriction decreases in oxidative damage to tissues (Yu, 1996). The previous reports have demonstrated that the calorie restriction reduces inflammations of dermatitis and the oxidative DNA damage derived from inflammation Tsuboi et al, 1998). In addition, the caloric restriction results in a decrease in the age-dependent accumulation of glycoxidation products, such as the pentosidine, in tissue (Cefalu et al, 1995;Iqbal et al, 1999;Reiser et al, 1994;Sell et al, 1997;Sell et al, 1996).…”
Section: Discussionmentioning
confidence: 99%